Fungsi Leadership dalam Pengelolaan Lembaga Pendidikan Islam - Fauziah, Nur (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
This article aims to look at the leadership function in Islamic educational institutions. The approach used in this paper is a qualitative approach using descriptive analysis and is library research (library research). Leadership is one of the factors that determine the vision, mission, and goals of an institution or organization. In the context of Islamic education institutions, one of the factors in the management of Islamic education institutions is the leadership of the school/madrasah principals, pesantren caregivers, deans, chancellors, and all elements of Islamic education are also very influential in their confidence in Islamic education.